Đánh giá khả năng bảo vệ thép của lớp phủ polyurea đi từ aspartic este gốc 4,4′-metylenbis-(2-metylcyclohexylamin) - Niếu, Nguyễn Hữu; Trí, Phan Minh; Thành, Nguyễn Đắc; Yến Oanh, Đoàn Thị (Vietnam Journal of Chemistry, 2017)
An aspartic ester was synthesized from 4,4’-methylenebis (2-methylcyclohexylamine), diethyl maleate and mono-epoxy. The method of synthesis, properties and structure of this material has been studied and published [1]. Aspartic ester mixed with additives to produce a 2-component polyurea coating system. Polyurea coating from aspartic ester cured by Desmodur N 3600 undergoes accelerated tests of environmental degradation by salt-fog and Q-sun. The metal protection capacity of the polyurea coating was evaluated through image, mechanical properties and electrochemical impedance before and after environmental acceleration. Keywords. Polyurea, aspartic ester, metal coating, coating protection.